(untitled) (Ciencias de la Ingeniería y Aplicadas, 2025)
In the Cuban nickel industry, wind and solar drying of laterites is implemented in an empirical way, which leads to inaccuracies in the estimation of moisture reduction achieved during the process. In this work, simulations of moisture distribution in piles of material exposed to natural drying were developed using models, algorithms and computer programs developed in previous works. The energy analysis showed that, on average, in the east and west slopes of the pile considered, moisture was reduced by 0.410 and 0.490 %, respectively. And in the complete pile the reduction was 0.450 % for a drying time of 12 hours, measured between 6 and 18 hours. The obtained behaviors suggest that during the natural drying process the moisture in the piles moves due to a mixed transport mechanism, which includes the combined effects of vapor diffusion, liquid diffusion and liquid movement